Language Portfolio as a tool for the development of communicative culture of students in upper secondary school - Rinemhota, Godfrey T.M.; Akbayeva, G.N.; Aliyeva, A.Z.; Kitibayeva, A.K. (Ye.A.Buketov Karaganda State University Publishing house, 2015)
The article considers the concept of «language portfolio», which makes it possible to expand the scope of training (classroom) process to include the experience of the students in authentic intercultural direct communication. What is very important for the formation of the ability to communicate on an intercultural level requires a constant search for the real yield on authentic communication. The article discusses the reflexive self-esteem of students, which reflects the level of knowledge, skills and competencies, as well as communicative culture.
Тілдік портфель орта мектебінің жоғары сынып оқушыларының коммуникативті мəдениетін дамыту құралы ретінде
Языковой портфель как инструмент развития коммуникативной культуры учащихся старших классов средней школы
Keywords: method; languages; portfolio; communicative culture; upper secondary school; approach; practice; pedagogic entity; motivation